The effect of deposition regimes of nanostructured nitride and carbonitride coatings on their structure, optical and electrophysical properties - Konstantinov, Stanislav V.; Komarov, Fadei F.; Chizhov, Igor V.; Zaikov, Valery A.; Zhyhulin, Dmitry V. (Journal of the Belarusian State University. Physics, 2024)
Nanostructured nitride (TiAlCuN) and carbonitride (TiAlCuCN) coatings were formed using the reactive magnetron sputtering method in various deposition regimes. The structure, morphology, optical and electrophysical properties of the obtained coatings, such as film thickness (h), average roughness (Sa), solar absorption coefficient (αs), emissivity (ε0), ratio of solar absorption coefficient to emissivity (αs/ε0), equilibrium temperature (Tр), photothermal conversion coefficient (η), surface resistance (R□), resistivity (ρ), plasma wavelength (λp), electron concentration (N) and charge carrier mobility (μ), were studied. It has been discovered that the resulting coatings are electrically conductive. The introduction of carbon into the composition of the TiAlCuN coating leads to a refinement of its structure and the formation of a predominantly globular morphology, making the material more uniform on surface and in depth. Coatings deposited using a target with a composition of 46 at. % Ti, 46 at. % Al, 8 at. % Cu, have higher solar absorption coefficient (by 32 %), emissivity (by 69 %) and photothermal conversion coefficient (by 31 %), lower ratio of solar absorption coefficient to emissivity (by 21 %) and equilibrium temperature (by 50 %), than samples obtained using a target with a composition of 69 at. % Ti, 23 at. % Al, 8 at. % Cu. It has been observed that the addition of copper to the composition of the TiAlN nitride under optimal deposition conditions leads to a decrease in the resistivity of the TiAlCuN coating by 4.0 –7.5 times compared to that of the TiAlN coating. Thus, the formed nanostructured TiAlCuN and TiAlCuCN coatings are promising for use as thermoregulatory ones for housings, systems and devices of small spacecrafts.
Keywords: reactive magnetron sputtering; nanostructured TiAlCuN and TiAlCuCN coatings; optical properties; electrophysical properties; space materials science